The Influence of Financial Literacy Level, Perception of Return and Technological Progress on Investment Interest of Millennial Generation in Central Jakarta - Fajar Riyadi Syawaluddin; Heri Ispriyahadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Capital markets play a significant role in enhancing a country's economic development, as well as national development. The millennial generation is expected to be the leader of growth in the economic field. This research uses quantitative methodology with the Partial Least Square Technique approach to test data instruments. The sample size was determined using Hair's formula. The research findings show that financial literacy has a positive and significant effect on millennials' investment interest, while perceived returns and technological advances have no significant effect on millennials' investment interest. The results of this study can be utilized by agencies and the government can work with the financial industry to help millennials understand investment work and help millennials understand financial concepts.